2019
DOI: 10.3389/fonc.2019.00323
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Chemotherapy Alters Neuropilin-1, PlGF, and SNAI1 Expression Levels and Predicts Breast Cancer Patients Response

Abstract: Circulating proteins hold a potential benefit as biomarkers for precision medicine. Previously, we showed that systemic levels of neuropilin-1 (NRP-1) and its associated molecules correlated with poor-prognosis breast cancer. To further identify the role of NRP-1 and its interacting molecules in correspondence with patients' response to neoadjuvant chemotherapy (NAC), we conducted a comparative study on blood and tissue samples collected from a cohort of locally advanced breast cancer patients, before and afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…It has been reported that the expression level of NRP-1 correlates with lymph metastasis (13,15) and inversely correlates with the survival in breast cancer (16). A recent study suggests that NRP-1 may be an independent prognostic factor for TNBC patients (43) and increased NRP-1 expression has been observed after neoadjuvant chemotherapy in breast cancer patients (44). All these studies highlight the significance and importance of NRP-1 in breast cancer, particularly, TNBC.…”
Section: Discussionmentioning
confidence: 91%
“…It has been reported that the expression level of NRP-1 correlates with lymph metastasis (13,15) and inversely correlates with the survival in breast cancer (16). A recent study suggests that NRP-1 may be an independent prognostic factor for TNBC patients (43) and increased NRP-1 expression has been observed after neoadjuvant chemotherapy in breast cancer patients (44). All these studies highlight the significance and importance of NRP-1 in breast cancer, particularly, TNBC.…”
Section: Discussionmentioning
confidence: 91%
“…Our previous studies demonstrated that NRP-1 acts as an oncogene in breast cancer progression [5][6][7][8]. Furthermore, recent evidence showed a close association of NRP-1 and breast cancer chemoresistance [9][10][11]. Collectively, the above mentioned findings indicate that NRP-1 is an crucial regulator in breast cancer pathogenesis and might be responsible for the chemoresistance-medicated by RP11-70C1.3/miR-6736-3p.…”
Section: Discussionmentioning
confidence: 76%
“…Previously, we reported that NRP-1 was frequently upregulated in breast cancer and functioned as an oncogene to accelerate tumorigenesis and progression by promoting proliferation, metastasis and stemness [5][6][7][8]. Recent studies revealed that NRP-1 could promote breast cancer cells resistance to ADM and PTX resistance through activation of ITGB3/FAK/NF-kB p65 axis and downregulation of BCRP/ABCG2 [9][10][11]. However, a more detailed role of NRP-1 upregulation in breast cancer pathogenesis has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…The overexpression of NRP‐1 triggered the up‐regulation of EMT‐related molecules vimentin and ZEB1, which is consistent with our previous finding that NRP‐1 is positively correlated with EMT (Adham et al, ). Recently, we showed that higher NRP‐1 levels in the plasma and tissue of breast cancer patients after NAC were correlated with reduced patient response and overall survival, respectively, and NRP‐1 knockdown in MDA‐MB‐231 cells improved the sensitivity of the cells to chemotherapy (Al‐Zeheimi et al, ). Although the transporter protein BCRP/ABCG2 is a known marker of multidrug resistance (Li, Chua, Kunnath, & Chowdhury, ), its expression in resistant MDA‐MB‐231 model was decreased while NRP‐1 and the downstream survival molecules were increased, indicating that BCRP/ABCG2 does not necessarily drive NAC resistance in the context of breast cancer.…”
Section: Discussionmentioning
confidence: 99%